Construyendo la identidad científica de la Didáctica de la Lengua y la Literatura: El necesario eclecticismo disciplinar. - López Valero, A.; Encabo Fernández, E. (Didáctica. Lengua y Literatura, 2000)
The aim of this work is to continue with a thought line already begun in recent articles. Through it, it's pretended to consolidate the ideas reported to the area of knowledge that supposed Language and Literature teaching. The discourse s central axle is situated about the neccesary disciplinary eclecticism to get that the area has got a coherence related to the planning and performance in educative action. 183 Amando h5¡,ez Valero Ct,osíruvendo la identidad cientifica de la Didácica de la Lengua... Eduardo Encabo Fernández There are different arcas coming together in Language and Literature Teaching; amongst it, Philology, Pedagogy, Sociology. Anthropology and pschicology. Wc will do a closeness to that arcas and will make and outline about the future ways through could spread the area.
Keywords: Teaching; Language and Literatu re Eclecticism; Identity Arcas